Comultiplication lattice modules - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2015)
Let M be a lattice module over the multiplicative lattice L. M is said to be a comultiplication L-module if for every element N of M there exists an element a is an element of L such that N = (O(M:M)a). Our objective is to investigate properties of comultiplication lattice modules.
Keywords: Multiplicative lattice; lattice modules; comultiplication lattice modules; PRIME ELEMENTS; MULTIPLICATION